Developing and validating an instrument to assess the current status of english language clubs (ELCs) in Malaysian secondary schools / Angel Helen Puspam ... [et al.] - Puspam, Angel Helen; Lee, Nagarajah; Chan Sue Lin, Valerie (2007)
It is believed that co-curricular activities can contribute to the holistic development of the students. As such, co-curricular activities form an important part of the school curriculum. Academic clubs are one of the components of the co-curricular activities and the English Language Club (ELC) is an example of an academic club. A vibrant and dynamic ELC can nurture and nourish language learnt in classroom with language used out-of-the classroom. The actual status of ELCs in this country is anyone's guess. Are they active? Are they merely drifting along aimlessly? Or are they defunct? It was under this cloud of uncertainty that this study was undertaken. It was aimed at producing an instrument to assess the current status of the English Language Clubs in the country.